Association of anti-Ro52 antibody positivity with interstitial lung disease and serological features in primary Sjögren’s disease - Mehmet Nur Kaya; Muhammed Canbaş; Özlem Kılıç; Ramazan Gümral; Sedat Yılmaz (Clinical and Experimental Medicine, 2026)
Abstract To investigate the association of anti-Ro52 antibody positivity with interstitial lung disease (ILD), serological findings, clinical manifestations, and treatment patterns in patients with primary Sjögren’s disease (SjD). This retrospective cross-sectional study included 205 patients with SjD. Patients were classified as anti-Ro52-positive or anti-Ro52-negative. Demographic features, clinical findings, laboratory variables, systemic involvement, and treatment patterns were compared between groups. Binary logistic regression analyses were performed to evaluate the independent association between anti-Ro52 positivity and ILD. Other between-group comparisons were considered exploratory and were adjusted for multiple testing using the Benjamini-Hochberg false discovery rate (FDR) procedure. Of the 205 patients, 101 (49.3%) were anti-Ro52 positive and 104 (50.7%) were anti-Ro52 negative. ILD was more frequent in anti-Ro52-positive patients than in anti-Ro52-negative patients (27.7% vs. 10.6%, p = 0.003). In univariable analysis, anti-Ro52 positivity was associated with ILD (OR 3.24, 95% CI 1.51–6.95, p = 0.002). This association remained significant after adjustment for age, sex, smoking status, and disease duration (adjusted OR 3.61, 95% CI 1.64–7.96, p = 0.001), and after further adjustment for anti-SSA positivity (adjusted OR 4.48, 95% CI 1.86–10.81, p < 0.001). Anti-Ro52-positive patients also had higher frequencies of anti-SSA positivity, anti-SSB positivity, and a speckled ANA pattern after FDR correction. Anti-Ro52 positivity was associated with a higher frequency of ILD and a distinct serological profile in SjD. These findings support its potential value in clinical phenotyping, although prospective multicenter studies are needed for validation.